Changes in bacterial populations and shrimp production in ponds treated with commercial microbial products - Devaraja, Thimmalapura N; Yusoff, Fatimah M; Shariff, Mohamed (Elsevier, 2002)
Commercial ponds receiving two microbial products were monitored for changes in bacterial populations and shrimp production. Nine ponds of 0.5 ha each were treated; three with microbial Product 1, three with Product 2 and three left untreated to serve as control ponds. The products were screened for species composition and administered following manufacturer's instructions throughout the culture period of 110 days. Product 1 contained Bacillus sp. and Saccharomyces sp. and Product 2 contained Bacillus sp., Nitrosomonas sp. and Nitrobacter sp. Water and sediment samples were collected once every 14 days for bacteriological analyses. Various heterotrophic (total plate count, presumptive vibrios, protein mineralising, ammonifying and sulphur reducing) and autotrophic (ammonia oxidising, nitrite oxidising, presumptive sulphur oxidising) bacterial groups were estimated for their population densities in water and sediment. Results showed that the Bacillus spp. were dominant in all ponds. Sediment of ponds treated with Product 1 had significantly higher (P<0.05) number of total plate count (1.24×106±0.27×106 cfu g−1) and presumptive sulphur oxidising bacteria (1.01×102±0.19×102 cfu g−1). The average density of sulphur reducing bacteria (2.74±0.27 cfu ml−1) in water of the control ponds was significantly lower (P<0.05) than that from treated ponds. The average production at the end of the culture period was relatively, but not statistically higher in ponds treated with Product 1 (5837.14±715.22 kg ha−1) when compared with those for Product 2 (4877.42±438.46 kg ha−1) and control (5102.28±262.28 kg ha−1) ponds. Some bacterial populations and feed conversion ratio (FCR) were significantly different in Product 1 ponds compared to others, but the economical returns were not statistically different between treatments. Further studies to show the benefits of using microbial products in commercial aquaculture farms should be conducted utilizing larger sample size.